2024
DOI: 10.1007/s00432-024-05610-y
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of positive pulmonary nodules based on machine learning algorithm combined with central carbon metabolism data

Jian-jun Liu,
Wen-bin Shen,
Qi-rong Qin
et al.

Abstract: Background Lung cancer causes a huge disease burden, and early detection of positive pulmonary nodules (PPNs) as an early sign of lung cancer is extremely important for effective intervention. It is necessary to develop PPNs risk recognizer based on machine learning algorithm combined with central carbon metabolomics. Methods The study included 2248 participants at high risk for lung cancer from the Ma'anshan Community Lung Cancer Screening cohort.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Oncometabolites make the tumor microenvironment more favorable for cell migration [36]. It has been shown that elevated plasma concentrations of succinic and maleic acid are associated with the development of lung cancer [37]. In the study by Ternes et al it was shown that gut microbial metabolite formate, produced by F. nucleatum, enhanced migration potential of HCT116 cells through the formation of focal adhesion points [38].…”
Section: Discussionmentioning
confidence: 99%
“…Oncometabolites make the tumor microenvironment more favorable for cell migration [36]. It has been shown that elevated plasma concentrations of succinic and maleic acid are associated with the development of lung cancer [37]. In the study by Ternes et al it was shown that gut microbial metabolite formate, produced by F. nucleatum, enhanced migration potential of HCT116 cells through the formation of focal adhesion points [38].…”
Section: Discussionmentioning
confidence: 99%